Different Types of Alcohol Tax and Minimum Pricing Policies: An Evidence and Policy Review - Jem Roberts; Katherine Severi; Peter Rice (Addicta: The Turkish Journal on Addictions)
To This article presents the best available evidence regarding types of alcohol taxation and alcohol pricing policies and their effectiveness in reducing alcohol harm, by reviewing scholarly and grey literature. The latest evidence shows that alcohol taxation, particularly when based on alcohol content, can be highly effec- tive at reducing alcohol consumption and subsequent harm, while providing governments with increased revenue. Minimum pricing policies can complement taxes by specifically targeting higher-risk drinking and reducing health inequalities. Alcohol taxes benefit population health as well as government revenue, and minimum pricing can complement taxes by setting limitations to commercial practices which undermine health goals.